Pengaruh Efektivitas Komite Audit terhadap Penghindaran Pajak - Rosalia Dira Christia; Jacobus Widiatmoko; Maria Goreti Kentris Indarti (Universitas Muhammadiyah Metro, 2025)
This study aims to examine the effect of audit committee effectiveness (size, frequency of work meetings, expertise, and independence of the audit committee) with profitability, leverage, and company size as control variables on tax avoidance. The population used is manufacturing companies in the consumer goods sector listed on the IDX in 2018-2021. Sampling using purposive sampling method and resulted in 228 selected samples. The data in this study are secondary data taken from the annual financial statements of manufacturing companies listed on the IDX in 2018-2021. Data analysis was carried out by descriptive analysis and multiple linear regression analysis. The results of this study indicate that the size of the audit committee, the frequency of work meetings, and the independence of the audit committee have a positive and significant effect on tax avoidance, but for audit committee expertise has a negative and significant effect on tax avoidance. Testing the control variables of profitability, leverage, and company size has no effect on tax avoidance.